2005
DOI: 10.1111/j.1349-7006.2005.00101.x
|View full text |Cite
|
Sign up to set email alerts
|

Orphan nuclear receptor DAX‐1 in human endometrium and its disorders

Abstract: DAX-1 (dosage-sensitive sex reversal adrenal hypoplasia congenita critical region on the X chromosome gene 1) is a recently characterized member of the orphan nuclear receptor family. DAX-1 functions as a global negative regulator of steroid hormone production. It inhibits adrenal 4 binding protein (Ad4BP)/steroidogenic factor-1 (SF-1) pathway-dependent P450arom expression in cultured human endometriotic stromal cells and acts as a corepressor for estrogen receptors (ER). In this study we first examined the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
26
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 52 publications
3
26
0
Order By: Relevance
“…In contrast, the knocked-down expression of NR0B1 did not affect the cell proliferation of A549 cells. This might be attributable to the difference of cell types; Saito et al 26 and Nakamura et al 28 did not find any correlation of NR0B1 expression level with the Ki-67 labeling index, a well-established marker for cell proliferative activity, in the endometrial adenocarcinoma of uterus and prostate. The present study on the clinical cases of lung adenocarcinoma showed that NR0B1 expression level did not correlate with the size of tumors.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In contrast, the knocked-down expression of NR0B1 did not affect the cell proliferation of A549 cells. This might be attributable to the difference of cell types; Saito et al 26 and Nakamura et al 28 did not find any correlation of NR0B1 expression level with the Ki-67 labeling index, a well-established marker for cell proliferative activity, in the endometrial adenocarcinoma of uterus and prostate. The present study on the clinical cases of lung adenocarcinoma showed that NR0B1 expression level did not correlate with the size of tumors.…”
Section: Discussionmentioning
confidence: 98%
“…26,28 Whereas, the subcellular localization of NR0B1 was various among cases with the present lung adenocarcinoma. Kawajiri et al 43 reported that NR0B1 localization changed during pituitary development from nucleocytoplasmic at embryonic day 10.5 to nucleus at day 18.5.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, DAX1 is known to act as a negative regulator of steroid production [10][11][12][13]. DAX1 has also been demonstrated to repress Ad4BP/SF-1-mediated transactivation of other steroidogenic genes, and to act as a corepressor for AR, PR, and ERβ [14][15][16][17][18][19][20]. These interactions could play significant roles by influencing sex-steroid signaling pathways.…”
mentioning
confidence: 99%